Availability and Usage of Electrophysical Agents by Portuguese Physiotherapists: an online Survey - Manuel Paquete; Pedro Harry Leite; Diana Bernardo; Luís Moreira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: The aim of this study is to describe the availability and usage of Electrophysical Agents (EPAs) by Portuguese Physiotherapists (PTs), and identify factors affecting its’ usage, such as PTs expertise, setting and autonomy.